Sport sponsorship from perspective of great industrial companies’ managers - İman Mırzaeı; Abdolrahman Mehdıpour; Tahereh Azmsha (Türk Spor ve Egzersiz Dergisi)
The objective of this research was to analysis the perspective of great industrial companies’ managers about effective factors on attracting sponsors in professional sport. According to this objective, the statistical population of this study included senior managers of all great industrial companies in Khuzestan province in Iran. The questionnaire of this study was a scholar-made questionnaire which its Content validity was confirmed by professors and sport management experts and its reliability and construct validity were also examined. In order to analyze the data of this research, exploratory factor analysis and path analysis methods were used by SPSS and Smart-PLS software. Exploratory factor analysis demonstrated that there are 4 factors attracting sponsors and these factors indicated 68/8% of total variance. These factors were “economic-marketing”, “media”, “legal and juridical” and finally “sport teams and spectators”. According to the final results of path analysis, media factor gained the first rank among 4 recommended total factors. Based on the findings of the present research, it is suggested that officials and managers of sport teams in order to attract sponsors from industrial companies, should have special attention to cases such as improve the quality and use of modern technology in live broadcasting of sport events, spreading media coverage of sport events, creating and using laws related to TV broadcasting rights, Employing famous players and coaches in sport teams and attracting more spectators.